State of the art on the conceptual modeling of serious games through a systematic mapping of the literature - Miguel, Juan (2022)
Serious games are those games whose objective is to stimulate learning or the acquisition of knowledge or a skill. Currently, there is a trend in the market towards the generation of this type of games. Given the importance of conceptualizing the domain of a problem and its solution, this paper presents the results of a systematic mapping of the literature, Systematic Mapping Study (SMS), with the purpose of identifying the state of the art and discovering the existing contributions regarding the conceptual modeling of serious games. A search was carried out in Scopus, IEEE Xplore and ACM digital libraries from January 2010 to June 2021. Of a total of 558 articles identified, 31 primary studies were analyzed. It was evidenced that the use of UML prevails for the modeling of serious games, mainly for class and activity diagrams, together with other languages such as UP4EG, DSML, Deterministic Finite Automaton (DFA), Discrete Event System Specification (DEVS) and Fuzzy Inference Systems (FIS). Thirty percent of the primary studies propose a framework and another 30% propose a development methodology. Most of these frameworks do not specify how to perform conceptual modeling.